Sulfur availability regulates plant growth via glucose-TOR signaling. Issue 1 (December 2017) - Dong, Yihan; Silbermann, Marleen; Speiser, Anna; Forieri, Ilaria; Linster, Eric; Poschet, Gernot; Allboje Samami, Arman; Wanatabe, Mutsumi; Sticht, Carsten; Teleman, Aurelio; Deragon, Jean-Marc; Saito, Kazuki; et al.
Abstract Growth of eukaryotic cells is regulated by the target of rapamycin (TOR). The strongest activator of TOR in metazoa is amino acid availability. The established transducers of amino acid sensing to TOR in metazoa are absent in plants. Hence, a fundamental question is how amino acid sensing is achieved in photo-autotrophic organisms. Here we demonstrate that the plant Arabidopsis does not sense the sulfur-containing amino acid cysteine itself, but its biosynthetic precursors. We identify the kinase GCN2 as a sensor of the carbon/nitrogen precursor availability, whereas limitation of the sulfur precursor is transduced to TOR by downregulation of glucose metabolism. The downregulated TOR activity caused decreased translation, lowered meristematic activity, and elevated autophagy. Our results uncover a plant-specific adaptation of TOR function. In concert with GCN2, TOR allows photo-autotrophic eukaryotes to coordinate the fluxes of carbon, nitrogen, and sulfur for efficient cysteine biosynthesis under varying external nutrient supply. Plants lack the amino acid sensors that regulate TOR in metazoans. Here Dong et al. show that Arabidopsis GCN2 senses carbon and nitrogen availability for cysteine synthesis while sulfur limitation activates TOR via glucose metabolism, providing a mechanism whereby plants control growth according to nutrient availability.